The facts of cassava - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The World Cassava Economy. Facts, trends and outlook FAO/IFAD, 2000. 66 pp. ISBN 925104399x US$12 E 13.95 FAO Sales and Marketing Group, Viale delle Terme di Caracalla, 00100 Rome, Italy. Fax: +39 06 57 05 33 60 Email: publications-sales@fao